Gender diversity and bank misconduct - Arnaboldi, F.; Casu, B.; Gallo, A.; Kalotychou, E.; Sarkisyan, A. (Journal of Corporate Finance, 2021)
This paper investigates whether gender-diverse bank boards can play a role in preventing costly misconduct episodes. We exploit the fines received by European banks from US regulators to reduce endogeneity issues related to supervisory and governance mechanisms. We show that greater female representation significantly reduces the frequency of misconduct fines, equivalent to savings of $7.48 million per year. Female directors are more influential when they reach a critical mass and are supported by women in leadership roles. The mechanism through which gender diversity affects board effectiveness in preventing misconduct stems from the ethicality and risk aversion of the female directors, rather than their contribution to diversity. The findings are robust to alternative model specifications, proxies for gender diversity, reverse causality, country and bank controls, and sub-sample analyses.